2022
DOI: 10.3390/ani12182479
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Administration of a Nutraceutical Supplement in Racehorses with Lower Airway Inflammation

Abstract: Mild–moderate equine asthma (MEA) is a chronic inflammatory disorder of the lower airways of the horse, characterized by tracheal mucus accumulation, cough and poor performance. The therapeutic approach is based on pharmacological treatment and environmental management. Moreover, the efficacy of the administration of antioxidant molecules has been reported. The aim of the present study was to evaluate the effect of the administration of a commercial nutraceutical supplement, composed of several herbal extracts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Other nutraceutical and herbal supplements for horses with EA have been studied, among other reasons, to avoid using pharmacological products forbidden in races or other sports. One nutraceutical product, a complementary feed containing maltodextrin, calcium carbonate, Arthrospira platensis (12%), and fermented pineapple (5%), supplemented with antioxidants, was studied recently [73], and it seems to improve the clinical score and mucus production. However, there were clinical differences between the nutraceutical and control groups at the beginning of the study that may have influenced these results.…”
Section: Use Of Supplementsmentioning
confidence: 99%
“…Other nutraceutical and herbal supplements for horses with EA have been studied, among other reasons, to avoid using pharmacological products forbidden in races or other sports. One nutraceutical product, a complementary feed containing maltodextrin, calcium carbonate, Arthrospira platensis (12%), and fermented pineapple (5%), supplemented with antioxidants, was studied recently [73], and it seems to improve the clinical score and mucus production. However, there were clinical differences between the nutraceutical and control groups at the beginning of the study that may have influenced these results.…”
Section: Use Of Supplementsmentioning
confidence: 99%
“…The study concluded that EIPH does not affect the athletic capacity of racehorses, and its role in decreased performance quality may follow a different pathway. Furthermore, the prospective case–control study by Stucchi et al [ 13 ] evaluates the efficacy of the administration of a nutraceutical supplement, composed of different herbal extracts with antioxidant properties, in Thoroughbred racehorses affected by MEA. The results show a reduction in tracheal mucus accumulation and clinical score in the treated patients.…”
mentioning
confidence: 99%